Nontypable Haemophilus influenzae displays a prevalent surface structure molecular pattern in clinical isolates. - Martí-Lliteras, P; López-Gómez, A; Mauro, S; Hood, D; Viadas, C; Calatayud, L; Morey, P; Servin, A; Liñares, J; Oliver, A; Bengoechea, J; Garmendia, J (2011)
Non-typable Haemophilus influenzae (NTHi) is a gram negative pathogen that causes acute respiratory infections and is associated with the progression of chronic respiratory diseases. Previous studies have established the existence of a remarkable genetic variability among NTHi strains. In this study we show that, in spite of a high level of genetic heterogeneity, NTHi clinical isolates display a prevalent molecular feature, which could confer fitness during infectious processes. A total of 111 non-isogenic NTHi strains from an identical number of patients, isolated in two distinct geographical locations in the same period of time, were used to analyse nine genes encoding bacterial surface molecules, and revealed the existence of one highly prevalent molecular pattern (lgtF+, lic2A+, lic1D+, lic3A+, lic3B+, siaA-, lic2C+, ompP5+, oapA+) displayed by 94.6% of isolates. Such a genetic profile was associated with a higher bacterial resistance to serum mediated killing and enhanced adherence to human respiratory epithelial cells.